Effectiveness and Safety of S-1-Based Therapy Compared with 5-Fluorouracil-Based Therapy for Advanced Colorectal Cancer: A Meta-Analysis. (27th November 2014) - Ye, Jiaxiang; Chen, Jiawei; Ge, Lianying; Liu, Aiqun; Zhou, Shaozhang
Abstract : Objectives. The aim of our study was to compare the efficacy and safety of S-1-based therapy (SBT) versus 5-fluorouracil-based therapy (FBT) for advanced colorectal cancer (ACRC). Methods. A meta-analysis of all eligible randomized controlled trials (RCTs) was performed using RevMan 5.1.0 software. Results. A total of 1625 patients from twelve RCTs including 820 patients in the SBT group and 805 patients in the FBT group were available for analysis. The meta-analysis of overall survival (hazards ratio HR = 0.94, 95% CI = 0.80–1.10), progression-free survival (HR = 1.03, 95% CI = 0.91–1.18), and overall response rate (odds ratio OR = 1.23, 95% CI = 1.00–1.53) showed no statistical significance between SBT group and FBT group. The statistically significant differences in the meta-analysis indicated less incidence of graded 3-4 neutropenia (OR = 0.49, 95% CI = 0.35–0.68) and nausea/vomit (OR = 0.41, 95% CI = 0.23–0.72) in the SBT group, and there was no statistically significant difference in the incidence of grade 3-4 anemia, thrombocytopenia, leucopenia, diarrhea, and treatment-related deaths between two groups. Conclusions. SBT had similar efficacy and better safety than FBT and was an attractive alternative to FBT for patients of ACRC, but further investigations in different populations would be needed to confirm it.